2019
DOI: 10.1039/c9ra06879a
|View full text |Cite
|
Sign up to set email alerts
|

Performance of metal–organic frameworks for the adsorptive removal of potentially toxic elements in a water system: a critical review

Abstract: This review examines the performance of metal–organic frameworks based on partition coefficient data over the classic maximum adsorption capacities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(37 citation statements)
references
References 168 publications
0
33
0
Order By: Relevance
“…To verify the accuracy of the proposed method, four real water samples including river water, lake water, pond water and farmland water spiked at four concentrations (5,20,50, and 100 ng mL À1 ) were analyzed. The recoveries were in the range of 85.6-118.2% with RSDs of 0.30-4.8% for all water samples (Table 2).…”
Section: Methods Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…To verify the accuracy of the proposed method, four real water samples including river water, lake water, pond water and farmland water spiked at four concentrations (5,20,50, and 100 ng mL À1 ) were analyzed. The recoveries were in the range of 85.6-118.2% with RSDs of 0.30-4.8% for all water samples (Table 2).…”
Section: Methods Validationmentioning
confidence: 99%
“…Among these SPE adsorbents, MOFs were possessed of high adsorption and separation performance, owing to their remarkable merits like large surface area, adjustable pore size, diverse structures, as well as great chemical and thermal stability. [19][20][21] On the other hand, polyHIPEs were also highly interconnected porous materials with distinct characteristics such as highly interconnected pore architecture, tunable porosity, controllable cavity, large surface areas, and adjustable functions, [22][23][24] however, depending on the high porosity poly-HIPEs for separation applications usually suffer from insufficient mechanical properties (strength, modulus and ductility). [25][26][27] Thus, enhancement of mechanical properties by using a variety of approaches, such as selecting new functional monomer systems, using medium internal phase emulsions instead of HIPEs to obtain higher density polyHIPEs, and especially combining HIPE templates with organic or inorganic particles to form composite structures, was very important to achieve improved polyHIPEs for separation applications.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the main peaks below 10° (2 theta) of the samples before and after Cs(I), adsorption is observed that those of the samples obtained after Cs(I) adsorption present smaller intensity and wider base of the peaks, suggesting that the Cs(I) ions, besides physical adsorption onto the surface of La‐ CPs, are removed from the aqueous solutions through chemical attraction by the anions and the used coligands Im and Phen from the CPs environment involving electrostatic interactions. [ 6–8 ]…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies showed that the coordination polymers (CPs) and its subdivision metal organic frameworks (MOFs) accomplish the desired properties and represent efficient adsorbent for the removal of various contaminants from aqueous solutions. [ 6–8 ]…”
Section: Introductionmentioning
confidence: 99%
“…The unique properties of MOFs and their structural tuneability [ 25 , 26 , 27 , 28 , 29 ] make these materials especially suitable for encapsulating a large variety of guest molecules, and hence they are promising candidates for a plethora of environmental and biomedical applications [ 30 , 31 , 32 , 33 , 34 , 35 ]. Restricting further discussion to the ability of MOFs to capture and remove toxic compounds from the environment, MOFs display all the desirable features in terms of water stability, porosity, and surface area, and can be used as alternate adsorbents for the adsorption and removal of toxic species [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. In addition to their capturing capacity, MOFs often have sensing properties, which are based on the change to the physical properties caused by the encapsulated metal ion [ 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%